2007
DOI: 10.1200/jco.2006.06.0244
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Phytoestrogens and Subsequent Breast Cancer Risk

Abstract: High genistein circulation levels are associated with reduced breast cancer risk in the Dutch population. No effects of lignans on breast cancer risk were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
97
1
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 146 publications
(104 citation statements)
references
References 35 publications
5
97
1
1
Order By: Relevance
“…The combined OR (summary OR ¼ 1.02, 95% CI ¼ 0.84 -1.23) from these three nested case -control studies is consistent with the finding of no association based on dietary soy isoflavones and breast cancer risk in Western populations. There were no differences in results by menopausal status (Horn-Ross et al, 2001;dos Santos Silva et al, 2004;Keinan-Boker et al, 2004;Bosetti et al, 2005;Fink et al, 2007;Verheus et al, 2007). One study examined the soy -breast cancer association by body size and reported no differences in results (Bosetti et al, 2005).…”
Section: Risk Association Studies In Low-soy-consuming Western Populamentioning
confidence: 97%
See 2 more Smart Citations
“…The combined OR (summary OR ¼ 1.02, 95% CI ¼ 0.84 -1.23) from these three nested case -control studies is consistent with the finding of no association based on dietary soy isoflavones and breast cancer risk in Western populations. There were no differences in results by menopausal status (Horn-Ross et al, 2001;dos Santos Silva et al, 2004;Keinan-Boker et al, 2004;Bosetti et al, 2005;Fink et al, 2007;Verheus et al, 2007). One study examined the soy -breast cancer association by body size and reported no differences in results (Bosetti et al, 2005).…”
Section: Risk Association Studies In Low-soy-consuming Western Populamentioning
confidence: 97%
“…To overcome the difficulties and imprecision associated with estimating low dietary soy intake from questionnaires, baseline, prediagnostic blood/urine isoflavone levels collected from participants of three cohorts were examined in relation to breast cancer risk (den Tonkelaar et al, 2001;Grace et al, 2004;Verheus et al, 2007); two of these studies also had information on dietary soy isoflavone intake (Grace et al, 2004;Keinan-Boker et al, 2004). The combined OR (summary OR ¼ 1.02, 95% CI ¼ 0.84 -1.23) from these three nested case -control studies is consistent with the finding of no association based on dietary soy isoflavones and breast cancer risk in Western populations.…”
Section: Risk Association Studies In Low-soy-consuming Western Populamentioning
confidence: 99%
See 1 more Smart Citation
“…[14][15][16][17][18][19][20][21] Two recently published metaanalyses (including our own) showed that high serum or urinary enterolactone levels were associated with a nonsignificant reduced postmenopausal breast cancer risk, whereas high consumption of dietary lignans was associated with a significant reduced postmenopausal breast cancer risk. 22,23 The objective of our study was to examine the association of the major serum enterolignan (enterolactone) with the risk of postmenopausal breast cancer in a large German study population with Western dietary habits.…”
mentioning
confidence: 99%
“…Evidence that these compounds are biologically active even at low levels in humans comes from interactions between phytoestrogens and gene variants of the estrogen receptor (ESR1 and NR1I2) (11,12), sex-hormone binding globulin (SHBG) (13), and probably aromatase (CYP19) (14). Recent studies have shown either increased or decreased breast cancer risk associated with phytoestrogens at low levels (15)(16)(17). However, these compounds can act as either estrogens or anti-estrogens, leading to concerns surrounding the use of phytoestrogen supplements in breast cancer patients (18,19).…”
Section: Introductionmentioning
confidence: 99%